Parameter-Dependency of Low-Intensity Vibration for Wound Healing in Diabetic Mice - Roberts, Rita E.; Bilgen, Onur; Kineman, Rhonda D.; Koh, Timothy J. (Frontiers in Bioengineering and Biotechnology, 2021)
Chronic wounds in diabetic patients represent an escalating health problem, leading to significant morbidity and mortality. Our group previously reported that whole body low-intensity vibration (LIV) can improve angiogenesis and wound healing in diabetic mice. The purpose of the current study was to determine whether effects of LIV on wound healing are frequency and/or amplitude dependent. Wound healing was assessed in diabetic (db/db) mice exposed to one of four LIV protocols with different combinations of two acceleration magnitudes (0.3 g, 0.6 g) and two frequencies (45 Hz, 90 Hz) or in non-vibration sham controls. The low acceleration, low frequency protocol (0.3g, 45 Hz) was the only one that improved wound healing, increasing angiogenesis and granulation tissue formation, leading to accelerated re-epithelialization and wound closure. Other protocols had little to no impact on healing with some evidence that 0.6 g accelerations negatively affected wound closure. The 0.3g, 45 Hz protocol also increased levels of insulin-like growth factor-1 and tended to increase levels of vascular endothelial growth factor in wounds, but had no effect on levels of basic fibroblast growth factor or platelet derived growth factor-bb, indicating that this LIV protocol induces specific growth factors during wound healing. Our findings demonstrate parameter-dependent effects of LIV for improving wound healing that can be exploited for future mechanistic and therapeutic studies.